Analisis Kepuasan Pengguna Sistem Informasi Akademik (Studi Kasus : UIN Raden Fatah Palembang) - Fathiyah Nopriani (Systemic: Information System and Informatics Journal, 2018)
Academic information system Online is applied throughout the faculties and postgraduates at Raden Fatah State Islamic University in Palembang with the address www.simak.radenfatah.ac.id in 2014. With the aim of measuring the user satisfaction of academic information systems Online using the EUCS method and measurement analysis using SPSS 24. The results of the analysis were obtained from the respondents' answers to users of Online academic information systems, namely lecturers and students of Raden Fatah State Islamic University Palembang where respondents were satisfied using the Online Academic Information System of Raden Fatah State Islamic University Palembang